2017
DOI: 10.18632/oncotarget.19866
|View full text |Cite
|
Sign up to set email alerts
|

Domain analysis reveals striking functional differences between the regulatory subunits of phosphatidylinositol 3-kinase (PI3K), p85α and p85β

Abstract: Our understanding of isoform-specific activities of phosphatidylinositol 3-kinase (PI3K) is still rudimentary, and yet, deep knowledge of these non-redundant functions in the PI3K family is essential for effective and safe control of PI3K in disease. The two major isoforms of the regulatory subunits of PI3K are p85α and p85β, encoded by the genes PIK3R1 and PIK3R2, respectively. These isoforms show distinct functional differences that affect and control cellular PI3K activity and signaling [1–4]. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…In our study, pan-PI3K (p85α) protein levels were repressed by enforced miR-106a-5p agomir in both differentiating and well-differentiated myotubes. PI3K (p85α), encoded by PIK3R1 gene, is a regulatory subunit of PI3Ks and essential for myoblasts proliferation and differentiation [ 24 , 38 ]. Germline deletion of the PIK3R1 gene leads to impaired muscle growth, and a significant reduction in muscle weight and fiber size [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, pan-PI3K (p85α) protein levels were repressed by enforced miR-106a-5p agomir in both differentiating and well-differentiated myotubes. PI3K (p85α), encoded by PIK3R1 gene, is a regulatory subunit of PI3Ks and essential for myoblasts proliferation and differentiation [ 24 , 38 ]. Germline deletion of the PIK3R1 gene leads to impaired muscle growth, and a significant reduction in muscle weight and fiber size [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are also consistent with work in other tumor and non-tumor models demonstrating a role for FOXC2 in the activation of PI3K-Akt-mTOR signaling (5,20,21), as we found that several genes associated with the PI3K-Akt signaling pathway (mmu04151) and the mTOR signaling pathway (mmu04150) were upregulated in B16-F1 as compared to its FOXC2-deficient counterpart. These genes include the Pik3r2 gene, which encodes the p85β regulatory subunit of PI3K known to induce oncogenic transformation and cellular proliferation (22,23), and the Insr gene, whose protein product drives various oncogenic activities through PI3K signaling (24). FOXC2 is also well-known for its ability to promote EMT and tumor cell migration/invasion (10,25), and our findings suggest potential mechanisms by which these hallmarks of cancer progression might be regulated by FOXC2 as well.…”
Section: Overview and Reuse Of Datamentioning
confidence: 66%
“…For p85α, deletion of the SH3 domain, not including PR1, has a strong activating effect that is seen in cellular transformation and in PI3K signaling. For p85β, the functional consequences of the SH3 truncation are not significant (67).…”
Section: N-terminal Deletions Of P85α and P85βmentioning
confidence: 99%
“…Deletion of the combined SH3 and BH domains leads in p85α to loss of the elevated activity seen with the SH3 truncation, and in p85β eliminates the enhanced oncogenic and signaling activities characteristic of the wild type protein (67). These truncations in essence create proteins that closely resemble the splice variants p50α and p55α and the p55γ isoform respectively of the regulatory subunits encoded by PIK3R1 and PIK3R3 .…”
Section: N-terminal Deletions Of P85α and P85βmentioning
confidence: 99%
See 1 more Smart Citation